Clean and healthy living behaviors and hypertension among elderly people in the community - Makmun, Armanto; Cahyani, Nafila; Sabir, Nurani Islami; Nirwana, Nirwana; Mulyadi, Melan Septiany; Husen, Siti Hajar Abdul (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Hypertension is a major public health problem among older adults and a leading contributor to cardiovascular morbidity and mortality in Indonesia. Clean and healthy living behavior (PHBS) has been recognized as a key preventive strategy for reducing lifestyle-related risk factors associated with hypertension, including unhealthy diet, physical inactivity, and poor health monitoring. Purpose: To determine the relationship between clean and healthy living behavior and the incidence of hypertension among elderly individuals at Maccini Sawah Health Center and Tamangapa Health Center. Method: A quantitative analytic observational study with a cross-sectional design was conducted. The study involved 98 elderly respondents recruited from Maccini Sawah Health Center (n=50) and Tamangapa Health Center (n=48). Clean and healthy living behavior status was assessed using a validated 12-item questionnaire, while hypertension was identified through medical records and direct blood pressure measurements. Data were analyzed using the Chi-Square test with a significance level of p<0.05. Results: The majority of respondents in both locations showed low levels of clean and healthy living behavior (63.3% overall). The prevalence of hypertension was 62.00% at the Maccini Sawah Community Health Center and 64.58% at the Tamangapa Community Health Center. Bivariate analysis showed that elderly individuals with low levels of clean and healthy living behavior had a significantly higher prevalence of hypertension (85.48%) compared to those with moderate (11.29%) and high (3.23%) levels. Statistical analysis revealed a highly significant association between clean and healthy living behavior and the incidence of hypertension (p=0.000). Conclusion: Clean and healthy living behaviors (Health-Based Drug Consumption Guidelines) are significantly associated with the incidence of hypertension among the elderly in Makassar City. Low adherence to clean and healthy living behaviors is a major risk factor, while moderate to high adherence is correlated with a lower prevalence of hypertension. Strengthening health promotion programs focused on clean and healthy living behaviors in primary healthcare settings is crucial to reduce the burden of cardiovascular disease and improve health outcomes for the elderly.